Measurement of The Direction of The Cemetery Qibla of Jerukgiling Village, Kendal Regency - Ahmad Farhan Makmur; Siti Qurrotul A'yuni (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research was conducted by students of KKN MIT TEMATIK 103 in Jerukgiling Village in response to the village apparatus's request to measure the direction of the Qibla of the local village tomb. This measurement aims to determine the accurate direction of the Qibla on the tomb, which has never been measured before. Measurements were performed using a qualitative method with a theodolite tool and analyzed using the LP2IF – RHI Version 1.0 qibla direction calculator. The measurement results show that the direction of the Qibla of the tomb is 294° 33' 15.91". This finding is expected to benefit the people of Jerukgiling Village by helping them carry out religious traditions related to burials.